KAJIAN ETNOSAINS KERAJINAN TEDUNG ROBROB DI DESA KEKERAN SEBAGAI PENDUKUNG MATERI PEMBELAJARAN IPA SMP - Bayu Suputra, Kadek; Pujani, Ni Made; Suardana, I Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the suboptimal utilization of local wisdom as a source of science learning in junior high schools, resulting in learning that remains abstract and less contextual. Tedung Robrob, a traditional craft from Kekeran Village, has the potential to be studied scientifically as a form of local wisdom. This research aims to (1) describe the process of making Tedung Robrob, (2) analyze the scientific concepts involved in its production, and (3) examine the relevance of these scientific findings to junior high school science learning materials. This study employs a descriptive qualitative method with an ethnoscience approach. The research was conducted in Kekeran Village, Buleleng Regency, Bali. The research subjects include craftsmen, Tedung Robrob business owners, and junior high school science teachers. Data were collected through observation, interviews, questionnaires, and documentation. The results show that the process of making Tedung Robrob consists of preparation of tools and materials, framework construction, painting of the umbrella parts, covering, and finishing. Within this process, several scientific concepts were identified, including those from biology, physics, and chemistry, such as classification of living organisms, classification of matter and its changes, simple machines, energy and its transformations, force, pressure, diffusion, heat and heat transfer, and environmental impacts. These findings are relevant to the Learning Outcomes (CP) and Learning Objectives (TP) in science education under the Merdeka Curriculum. Therefore, Tedung Robrob can be utilized as a contextual, ethnoscience-based learning resource to enhance students’ conceptual understanding, critical thinking skills, and learning motivation in junior high schools